Perbandingan Latihan foward Squat Jumps Dengan Short Run-up Triple Jump Terhadap Peningkatan Power Tungkai - Nurani, Alini; Kurniawan, Asep Ridwan; Nurzaman, Muhammad (Jurnal Keolahragaan, 2024)
ABSTRACTThis study aims to determine the impact of forward squat jumps training with short run-up triple jump training on increasing leg power. The research method used is pre-experimental design. The research location is SD Negeri 2 Bojongmengger, Ciamis Regency. The research sample consisted of 26 girls who were members of extracurricular volleyball. The sampling technique uses total sampling. Based on data analysis using SPSS series 26, the results are: 1. Forward squat jumps training has a significant influence on increasing leg power in female students at SD Negeri 2 Bojongmengger, Ciamis Regency. 2. The short run-up triple jump exercise had a significant influence on increasing leg power in female students at SD Negeri 2 Bojongmengger, Ciamis Regency. 3. There is a significant difference between forward squat jumps and short run-up triple jumps on increasing leg power in female students at SD Negeri 2 Bojongmengger, Ciamis Regency. The conclusion is that forward squat jumps training with short run-up triple jumps has a significant effect on increasing leg muscle explosive power. Suggestion: It is hoped that there will be research involving male students because it can be seen that when carrying out research in the field, male students also tend to have a sense of interest and are inspired to try to carry out movements on both variables and the test instrument.